The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1007/bf00042034
|View full text |Cite
|
Sign up to set email alerts
|

Expression of three osmotin-like protein genes in response to osmotic stress and fungal infection in potato

Abstract: We have characterized three cDNAs encoding osmotin-like proteins from potato (Solanum commersonii) cell cultures. These cDNAs (pA13, pA35, and pA81) have extensive nucleotide identity in the coding regions but low homology in the 3' non-coding sequences, and may encode three isoforms of potato pathogenesis-related (PR) type 5 proteins. Using gene-specific probes, RNA gel blot analyses showed constitutive accumulation of osmotin-like protein mRNAs in cell cultures, leaves, stems, roots and flowers, with high ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
72
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 43 publications
7
72
0
1
Order By: Relevance
“…5). These genes have been previously reported to be salt stress inducible in different species (Zhu et al, 1995;Nylander et al, 2001;Pendranzani et al, 2003). We observed that NH 4 + treatments induced RD22 mRNA accumulation in the absence of salt stress and that RD22 mRNA accumulation in response to salt stress lightly increased after salinity in both treatments (Fig.…”
Section: Nh 4 + Treatment Induces the Main Hormone Signaling Pathwaysmentioning
confidence: 76%
“…5). These genes have been previously reported to be salt stress inducible in different species (Zhu et al, 1995;Nylander et al, 2001;Pendranzani et al, 2003). We observed that NH 4 + treatments induced RD22 mRNA accumulation in the absence of salt stress and that RD22 mRNA accumulation in response to salt stress lightly increased after salinity in both treatments (Fig.…”
Section: Nh 4 + Treatment Induces the Main Hormone Signaling Pathwaysmentioning
confidence: 76%
“…Cold-induced accumulation of chitinase has been observed in barley (Tronsmo et al, 1993) and bermudagrass (Gatschet et al, 1996). Moreover, low temperature has been shown to increase accumulation of three mRNAs in potato that correspond to transcripts of cDNAs encoding osmotin-like proteins (Zhu et al, 1995). These proteins are also known as PR-5 proteins and are similar to TLPs (Zhu et al, 1995).…”
mentioning
confidence: 99%
“…Moreover, low temperature has been shown to increase accumulation of three mRNAs in potato that correspond to transcripts of cDNAs encoding osmotin-like proteins (Zhu et al, 1995). These proteins are also known as PR-5 proteins and are similar to TLPs (Zhu et al, 1995). Although a 67-kD AFP was purified recently from the bittersweet nightshade Solanum dulcamara, this protein showed no similarity to other proteins (Duman, 1994).…”
mentioning
confidence: 99%
“…Among stress proteins are osmotin and osmotin-like proteins that have also been classified as members of plant PR type-5 proteins (Singh et al, 1989;BOI et al, 1990;Zhu et al, 1993Zhu et al, , 1995. It has been demonstrated that tobacco osmotin gene expression is activated by ABA, NaC1, wounding, vira1 infection, and ethylene (LaRosa et al, 1992;Nelson et al, 1992).…”
mentioning
confidence: 99%